Edukasi Penggunaan Tempat Tidur - Pomarida Simbolon; Tri Carolina Laia; Leoni Putri Cantika Hulu (Yayasan Literasi Sains Indonesia, 2025)
Inpatient services can affect the level of efficiency in hospitals that aim to restore the condition of sick patients. Inpatient Units (URI) have an important role for hospitals, because most of the income received in hospitals is from inpatient services. Outpatient units, inpatient units, emergency units, maintenance service units and others are health service activities in hospitals. The indicators owned by each unit have been set to measure the quality and efficiency of services that have been carried out in hospitals. The indicator used to assess the level of efficiency of hospital management is the inpatient service indicator. The indicators used in inpatient units consist of four (4) indicators, including indicators of the level of management efficiency that can be measured by the BOR parameter, namely the size of the bed utilization rate, the high and low levels of bed utilization can be seen from the BOR results. BTO is the frequency of bed use in a period, meaning how many times the bed is used in a certain time. The purpose of education for Stikes Santa Elisabeth Medan students is to increase knowledge and insight regarding the efficiency of bed use in hospitals.